Penerapan Teknik Solution Focus Brief Counseling (SFBC) melalui Konseling Kelompok dalam Mengurangi Dampak Negatif Smartphone Kelas XI di UPT SMAN 9 Makassar - Suriani, Lili (Indonesian Journal of School Counseling: Theory, Application, and Development, 2022)
This study aims to determine the effectiveness of using Solution Focus Brief Counseling Techniques in reducing negative impact smartphone through group counseling services. This research approach is qualitative. This type of research uses Guidance and Counseling Action Research. The group counseling service carried out includes four stages, namely the initial, transition, core and termination stages and for the Solution Focus Brief Counseling it has 6 stages which generally help students replace negative thoughts that make anxious thoughts more positive. The object of this research is 8 students of 9th grade who experience negative impact smartphone. The results showed that the application of Cognitive Restructuring techniques can reduce negative impact smartphone which is indicated by changes in student behavior and being able to set meaningful personal goals and solve their problems about negative impact smartphone.